Short-term complications of anesthetic technique used in hip fracture surgery in elderly people - Afsaneh Norouzi; Fozhan Behrouzibakhsh; Alireza Kamali; Bijan Yazdi; Babak Ghaffari (PAGEPress Publications, 2018)
Postoperative complications of fracture are one of the main problems in older patients with hip fracture. In this study, complications were observed 48 hours after surgery in different anesthetic procedures. This prospective cross sectional study was carried out over a 12-month period. All subjects over 55 years of age undergoing hip fracture surgery were selected for study with ASA class (American Society of Anesthesiology: one, two and three). After determining the vital signs in the operating room, anesthesia type (general, spinal and epidural) and various variables were recorded. It was observed that the spinal anesthesia method had the lowest level of postoperative disturbances of consciousness and had the shortest duration in terms of duration of time. On the other hand, general anesthesia was the least in terms of blood transfusion. Finally, epidural anesthetic method showed the least amount of pain 48 hours after operation and the least changes in blood pressure and heart rate.